Policy Networks in the Implementation of ‘Cities Without Slums’ Program in Baleendah District, Bandung Regency - Ahmad Hadi; Budiman Rusli; M. Benny Alexandri (Jurnal Administrasi Publik (Public Administration Journal), 2020)
This study is entitled Policy Network in the Implementation of ‘Cities Without Slums’ Program (KOTAKU) in Baleendah District, Bandung Regency. This study is motivated by the author's interest in the implementation of the KOTAKU program, which is a collaborative platform program but in its implementation there are still problems related to coordination and participation in achieving the goals of ‘cities without slums’ program. This study used descriptive research method with a qualitative approach, and the results of studywere obtained from library research and field studies, namely observation, documentation, and interviews. This study used the Deleon and Varda policy network theory which consists of several characteristics: representation, reciprocity, horizontal power structure, embeddedness, trust and formality, participatory decision making, and collaborative leadership. Based on the results of this study, it can be concluded that the Policy Network in the Implementation of the KOTAKU Program in Baleendah District, Bandung Regency is not optimal because some of the characteristics that exist in the policy network are representation, horizontal power structure and collaborative leadership.